On the stepanov almost periodic solution of a second-order infinitesimal generator differential equation - Aribindi Satyanarayan Rao (International Journal of Mathematics and Mathematical Sciences)
The Stepanov almost periodic solution of a certain second-order differential equation in a reflexive Banach space is shown to be almost periodic.